HUBUNGAN POLA MAKAN, AKTIVITAS FISIK, IMT, STRESS, PEKERJAAN, DAN DUKUNGAN KELUARGA DENGAN DIABETES MELITUS - Br Purba, Debora May Sary; Nadapdap, Thomson P.; Siahaan, Jekson Martiar (Universitas Methodist Indonesia, 2021)
Background : Diabetes mellitus (DM) has symptoms of hyperglycemia, which is a medical condition when blood glucose levels increase exceeding normal values. The International Diabetes Federation predicts that the prevalence rate will continue to increase until reach 578 million people in 2030 and reach 700 million in 2045. The purpose of method was to clarify the relationship between several variables such as physical activity, BMI, diet, stress, work, and support from families with DM. Methods: This research was conducted by between using a literature review method that focuses on the results of writing related to the relationship physical activity, BMI, diet, stress, work, and family support with DM through searching journal sites such as Google Schoolar, Google, and Pubmed, in the period 2016-2021. Data obtained from previous research. Analysis of research data was complated by between using problem of interest, intervention, comparison, outcome techniques. Results: There were found 11 journals, appropriate with inclusion criteria. There were significant relationship between diet (2 journals), physical activity (4 journals), BMI (2 journals), stress (1 journal), job (1 journal), and family support (2 journals) in patients with DM. The study obtained a p value <0.05 which stated that there was there significant relationship between physical activity, BMI, diet, stress, work, and family support with DM. Conclusion: The results explain there is a relationship between physical activity, BMI, diet, stress, job, and family support with DM.